2021
DOI: 10.1136/bmj.n49
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective validation of Canadian TIA Score and comparison with ABCD2 and ABCD2i for subsequent stroke risk after transient ischaemic attack: multicentre prospective cohort study

Abstract: Objective To validate the previously derived Canadian TIA Score to stratify subsequent stroke risk in a new cohort of emergency department patients with transient ischaemic attack. Design Prospective cohort study. Setting 13 Canadian emergency departments over five years. Participants 7607 consecutively enrolled adult patients attending the emergency department w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
2
20
0
4
Order By: Relevance
“…CVEs in the UVP group. Although, recently, some studies have found a low reliability of the ABCD2 score in identifying patients with a CVE [50][51][52], it has been suggested that it might be useful when used in combination with other clinical signs [53] This is also supported by data from the present study, since the sensitivity for the detection of a CVE decreased (87.6 vs. 93.8%) when the ABCD2 criterion was excluded. Overall, we feel that the approach used in the PoiSe diagnostic algorithm adequately considers the existing evidence of a high stroke risk in specific subgroups of patients with vertigo and…”
Section: Detection Of a Cvesupporting
confidence: 83%
“…CVEs in the UVP group. Although, recently, some studies have found a low reliability of the ABCD2 score in identifying patients with a CVE [50][51][52], it has been suggested that it might be useful when used in combination with other clinical signs [53] This is also supported by data from the present study, since the sensitivity for the detection of a CVE decreased (87.6 vs. 93.8%) when the ABCD2 criterion was excluded. Overall, we feel that the approach used in the PoiSe diagnostic algorithm adequately considers the existing evidence of a high stroke risk in specific subgroups of patients with vertigo and…”
Section: Detection Of a Cvesupporting
confidence: 83%
“…We found that 16.3% of the CTAs done during the post-intervention period had a clinically significant abnormality and more neurology consultations were completed in the ED. More work on using different clinical triaging tools to select high-risk patients who may benefit from CTA [21], or neurology consultation in the ED, and further effort to improve patient flow in the ED for patients with TIA or minor stroke are needed.…”
Section: Strengths and Lessonsmentioning
confidence: 99%
“…The Canadian TIA Score (Figure 2) has been derived and validated in 2 large, multicentre cohort studies to accurately stratify patients with TIA or minor stroke as low-, medium-or high-risk for a subsequent stroke within 7 days. 16,17 Low-risk patients have a risk of less than 1%, medium-risk patients have a 1%-5% risk and high-risk patients have a risk of more than 5% for a subsequent stroke within 7 days. A reasonable clinical approach is to arrange urgent vascular imaging for medium-and high-risk patients, and to discuss high-risk patients with a stroke specialist during their initial evaluation.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…The Canadian TIA Score outperformed both the ABCD2 (age, blood pressure, clinical features, duration of symptoms and diabetes) and the ABCD2i (age, blood pressure, clinical features, duration of symptoms, diabetes and infarction) scores, which are relatively simple and widely recognized tools (absolute net reclassification index, which quantifies how well a new model reclassifies cases compared with an old model, of 12.0% and 8.5% over ABCD2 and ABCD2i, respectively; 16.3% of patients classified as low risk with Canadian TIA Score v. 0% classified as low risk using ABCD2 or ABCD2i). 16…”
Section: Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation